2019
DOI: 10.1007/s10787-019-00655-9
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the phagocyte NADPH oxidase/NOX2 and myeloperoxidase in the mouse brain during pilocarpine-induced temporal lobe epilepsy and inhibition by ketamine

Abstract: Excessive reactive oxygen species (ROS) production can induce tissue injury involved in a variety of neurodegenerative disorders such as neurodegeneration observed in pilocarpine-induced temporal lobe epilepsy. Ketamine, a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist has beneficial effects in pilocarpine-induced temporal lobe epilepsy when administered within minutes of seizure to avoid the harmful neurological lesions induced by pilocarpine. However, the enzymes involved in ROS productions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…These problems are likely to become hot spots and directions for future studies. Fatma’s team found that ketamine has beneficial effects on pilocarpine-induced temporal lobe epilepsy in mice and that administration within minutes of seizures avoids nerve damage caused by pilocarpine ( Tannich et al, 2020 ). However, the specific mechanism of epilepsy is unclear, and there is a lack of clinical studies on ketamine in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…These problems are likely to become hot spots and directions for future studies. Fatma’s team found that ketamine has beneficial effects on pilocarpine-induced temporal lobe epilepsy in mice and that administration within minutes of seizures avoids nerve damage caused by pilocarpine ( Tannich et al, 2020 ). However, the specific mechanism of epilepsy is unclear, and there is a lack of clinical studies on ketamine in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 9 Consistently, elevated expression of NOX2 was revealed in brain tissues from mice model of epileptic ictus or middle cerebral artery occlusion (MCAO). 10 , 11 Also, NOX2 expression by astrocytes was significantly higher in TBI patients than in controls. 12 Overall, it is speculated that NOX2 may represent a potential biomarker of acute brain injury.…”
Section: Introductionmentioning
confidence: 91%
“…[137] MPO expression is low in the normal brain, whereas MPO levels are substantially upregulated in epileptic regions. [138] It can catalyze hydrogen peroxide (H 2 O 2 ) and Clto produce HClO and other oxides, which can further activate MMPs to destroy the BBB, and increase OS in the brain. Zhang et al [139] verified that MPO increases in the corresponding brain tissue and that blocking MPO activity could delay and reduce seizures.…”
Section: Myeloperoxidase-responsive Probesmentioning
confidence: 99%